2014
DOI: 10.1186/1471-2458-14-545
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for low high-density lipoprotein cholesterol levels in Australian indigenous peoples: a systematic review

Abstract: BackgroundLow plasma high-density lipoprotein cholesterol (HDL-C) levels are a strong, independent, but poorly understood risk factor for cardiovascular disease (CVD). Although this atherogenic lipid abnormality has been widely reported in Australia’s Indigenous peoples, Aboriginal and Torres Strait Islanders, the evidence has not come under systematic review. This review therefore examines published data for Indigenous Australians reporting 1) mean HDL-C levels for both sexes and 2) factors associated with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
0
13
0
2
Order By: Relevance
“…The importance of social factors — education, inequities in resource allocation, employment opportunities, physical infrastructure — must also be taken into account . Finally, genetic and inflammatory factors play important roles in determining serum lipid levels in Indigenous Australians . In a medium‐sized study in southeast Queensland ( N = 155), apolipoprotein E4 polymorphisms associated with high triglyceride and low HDL‐cholesterol levels were 80% more frequent among Indigenous than among non‐Indigenous participants …”
Section: Discussionmentioning
confidence: 99%
“…The importance of social factors — education, inequities in resource allocation, employment opportunities, physical infrastructure — must also be taken into account . Finally, genetic and inflammatory factors play important roles in determining serum lipid levels in Indigenous Australians . In a medium‐sized study in southeast Queensland ( N = 155), apolipoprotein E4 polymorphisms associated with high triglyceride and low HDL‐cholesterol levels were 80% more frequent among Indigenous than among non‐Indigenous participants …”
Section: Discussionmentioning
confidence: 99%
“…There are around 290 million patients with cardiovascular diseases in China, accounting for 40% of disease deaths, presenting tremendous difficulties in prevention and treatment of the disease. Dyslipidemia, especially elevated levels of low-density lipoprotein cholesterol (LDL cholesterol, or LDL-C), is the major factor for ASCVD [1][2] , making it the primary subject in the prevention and treatment of cardiovascular diseases to control blood lipids. In the Chinese Guidelines on Prevention and Treatment of Dyslipidemia in Adults issued in 2016, LDL-C was regarded as the most important indicator for early warning, medication modification, and lipid monitoring in ASCVD patients.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Previous studies have confirmed that dyslipidemia, especially increased low-density lipoprotein (LDL) cholesterol (LDL-C) levels, is the most important risk factor for ASCVD, including coronary artery disease (CAD). 2 , 3 ASCVD is a well-known inflammatory disease that is also related to oxidative stress. 4 Previous data have shown that inflammation is an important feature of atherosclerotic lesions.…”
Section: Introductionmentioning
confidence: 99%